2021
DOI: 10.3390/v13020280
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human Papillomavirus (HPV) Genotypes in HIV-Negative and HIV-Positive Women with Cervical Intraepithelial Lesions in the Eastern Cape Province, South Africa

Abstract: South African women have a high rate of cervical cancer cases, but there are limited data on human papillomavirus (HPV) genotypes in cervical intraepithelial neoplasia (CIN) in the Eastern Cape province, South Africa. A total of 193 cervical specimens with confirmed CIN from women aged 18 years or older, recruited from a referral hospital, were tested for HPV infection. The cervical specimens, smeared onto FTA cards, were screened for 36 HPV types using an HPV direct flow kit. HPV prevalence was 93.5% (43/46) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 54 publications
4
33
1
Order By: Relevance
“…It is important to note that among women of African ancestry origin, HPV-35 is detected in approximately 10% of cervical cancer cases, while it is detected in approximately 2% of worldwide cases [ 1 , 21 , 22 ]. Studies in Sub-Saharan African populations have reported an HPV-35 prevalence of up to 40% among women with cervical intraepithelial neoplasia (CIN) or cervical cancer [ 21 , 31 , 35 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that among women of African ancestry origin, HPV-35 is detected in approximately 10% of cervical cancer cases, while it is detected in approximately 2% of worldwide cases [ 1 , 21 , 22 ]. Studies in Sub-Saharan African populations have reported an HPV-35 prevalence of up to 40% among women with cervical intraepithelial neoplasia (CIN) or cervical cancer [ 21 , 31 , 35 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data needs to come from population-based surveillance and women with cervical disease in unvaccinated women. Information on the prevalence of HPV and the distribution of HPV types in women residing in the Eastern Cape Province of South Africa is limited [ 31 ] and based on cervical specimens collected by cervical brush. The current report presents HPV genotyping data in cervical biopsies and this is significant because HPV types detected in cervical biopsies are more likely to be integrated into tissue and associated with the observed lesion.…”
Section: Introductionmentioning
confidence: 99%
“…AIDSassociated mortality has decreased signifi cantly since the introduction of "Antiretroviral Therapy" (ART), and HIVpositive women's life expectancy has almost equalled that of HIV-negative women [105]. Hence, the population of HIVinfected women has upsurge from 3.3 million to 18.8 million between 1990 to 2018, with 60% of these women living in A study in South Africa by Taku, et al [109] reported that HIV-positive women with CIN3+ and CIN2+ had an HPV prevalence of 96.6% (142/147) and 93.5%(43/46), respectively. Furthermore, HPV prevalence was substantially higher in women living with HIV than those without HIV, and lastly, multiple types were found to be more common in women living with HIV than those without HIV (p = 0.034).…”
Section: Socio-cultural Factorsmentioning
confidence: 99%
“…These viruses include human Metapneumo virus (hMPV), Respiratory syncytial virus (RSV), severe fever with thrombocytopenia syndrome virus (SFTSV), Hanta virus (HTNV), Sin Nombre virus (SNV), avian Influenza A strain (H7N9), Ebola virus, Zika virus, Nipah virus, Hepatitis viruses, West Nile fever virus, Lujo virus, Lassa virus (LASV), Dengue virus (DENV), and Chikungunya virus (CHIKV), to name only a few [5][6][7][8]. One point to note is that these viruses are, on top of other 'common' viruses like Human immunodeficiency virus (HIV) and human Papilloma virus (HPV), currently infecting millions of people, but not attracting a great deal of general attention, probably because they have been around for some time and at least some forms of treatment are now available for them [9]. For instance, Acquired Immunodeficiency Syndrome (AIDS), caused by HIV, was first recognized as a new disease in 1981 and has since been responsible for at least 60 million infections and at least 25 million deaths [10].…”
Section: Introductionmentioning
confidence: 99%